Prevalence, Antibiotic Susceptibility and Diversity of Vibrio parahaemolyticus Isolates in Seafood from South China - Yang, Ying; Xie, Jiafang; Li, Hua; Tan, Shuwen; Chen, Yanfeng; Yu, Hui (Frontiers in Microbiology, 2017)
Vibrio parahaemolyticus is a leading cause of foodborne infections in China and a threat to human health worldwide. The main objective of this study is to determine the prevalence and characteristic of V.parahaemolyticus isolates in fish, oyster and shrimp samples from the South China domestic consumer market. To accomplish this, we examined 504 seafood samples from 11 provinces of China. The prevalence rates were 9.38%, 30.36%, and 25.60%, respectively. In summer (33.33%), the prevalence of V.parahaemolyticus was more common than that detected in the winter (14.01%). In addition, we identified 98 V.parahaemolyticus strains. The antimicrobial resistance trends of our seafood isolates to 15 antimicrobial agents revealed that major isolates were resistant to ampicillin (79.59%). Furthermore, 68.38% of the isolates were identified as being multidrug resistance. The prevalence of tdh or trh genes among the isolates was 8.16% and 12.24%, respectively. ERIC-PCR and MLST results enabled classification of the isolates (n = 98) into different clusters, revealing genetic variation and relatedness among the isolates. Thus, our findings demonstrate the prevalence of V . parahaemolyticus in a variety of common seafood consumed domestically in China and provides insights into the dissemination of antibiotic-resistant strains, which should improve our microbiological risk assessment knowledge associated with V. parahaemolyticus in seafoods.